An analysis of competition law implementation in the EAC, SADC, and COMESA and the problem of overlapping membership - Khabo, Lebona (Department of Commercial Law, 2020)
Competition law is an integral building block in the attainment of regional integration, with Regional Economic Communities (RECs) on the continent making specific provision for competition policy in their founding and developmental agreements. However, in the Southern African Development Community (SADC), the East African Community (EAC) and the Common Market for Eastern and Southern Africa (COMESA), Partner and Member states have implemented competition law in varying degrees, in some cases there is a complete vacuum. In this paper I wish to analyse the development and implementation of competition law in the respective regions, by dissecting the manner in which the regions have gone about promoting competition law in the regions, I shall further analyse the domestic development of competition law in some of the Partner and Member States. Due to the voluntary nature of the RECs some Member and Partner States of SADC and the EAC are also members of COMESA, this creates a multiplicity of regional obligations as well as domestic obligations. In light thereof I will further analyse the effect of overlapping membership of RECS, and whether it creates any unintended problems, and if so, how this has been dealt with or can be dealt with.